ESTIMATION OF MEAN ARTERIAL PRESSURE BY THE ANALYSIS OF BRACHIAL PULSE WAVEFORM RECORDED BY APPLANATION TONOMETRY AND COMPARISON WITH CURRENTLY USED ALGORITHMS. (April 2021) - Grillo, Andrea; Colapietro, Nina; Salvi, Paolo; Furlanis, Giulia; Baldi, Corrado; Rovina, Matteo; Salvi, Lucia; Faini, Andrea; Bilo, Grzegorz; Fabris, Bruno; Carretta, Renzo; Benetos, Athanase; et al.
Abstract : Objective: Mean arterial pressure (MAP) is usually calculated by adding one third of pulse pressure (PP) to diastolic blood pressure (DBP). This formula assumes that the average waveform of pulse pressure (PP) is constant in all individuals and 33.3% of PP is needed to obtain MAP (MAP = DBP + PPx0.333). Other empirical formulas were proposed to calculate MAP, by adding to DBP a different established percentage of PP: MAP = DBP + PPx0.40; MAP = DBP + PPx0.412; MAP = DBP + PPx0.333 + 5mmHg. The estimation of MAP by considering a fixed relationship between SBP and DBP may not be appropriate in the single patient, if significant inter-individual and intra-individual variations occur in the pressure waveform. Design and method: We evaluated the inter-individual variations in MAP calculated from the integral of brachial pressure waveform recorded by applanation tonometry in 1526 patients belonging to 3 distinct cohorts: elderly, hypertensive, and normotensive adults, and the intra-individual variations in 19 healthy controls after a mental stress test. Results: The percentage of PP required to be added to DBP to obtain MAP was extremely variable among individuals, ranging from 23% to 58% (mean: 42.2 ± 5.5%), was higher in females (42.9 ± 5.6%) compared to males (41.2 ± 5.1%, p < 0.001), lower in the elderly cohort (40.9 ± 5.3%) than in the general population cohort (42.8 ± 6.0%, p < 0.001) and in the hypertensives (42.4 ± 4.8%, p < 0.001). This percentage was significantly associated with DBP (b = 0.357, p < 0.001) and gender (b = 0.203, p < 0.001). A significant increase in this percentage (from 39.9 ± 3.2 to 43.0 ± 4.0, p < 0.0001) was found in 19 volunteers, after mental stress test, and was significantly correlated to the increase in blood pressure and heart rate (p = 0.001). MAP value assessed on the brachial tonometric curve was compared with the MAP estimated by formulas proposed in the literature: the average bias from tonometric MAP (mean ± 1.96xSD) was: -5.0 ± 6.7 mmHg when MAP = DBP + PPx0, 333; -1.2 ± 6.1 mmHg when MAP = DBP + PPx0.40; -0.6 ± 6.1 mmHg when MAP = DBP + PPx0.412; -0.4 ± 6.7 mmHg when MAP = DBP + PPx0.333 + 5. Conclusions: Due to high interpersonal variability, the estimation of MAP based on fixed formulas is unreliable and inadequate. An improvement in the evaluation of MAP is advisable in daily clinical practice and may be based on the analysis of brachial pulse waveform.